Brain Lipid Binding Protein in Axon-Schwann Cell Interactions and Peripheral Nerve Tumorigenesis - Miller, Shyra J. (American Society for Microbiology, 2003)
Loss of axonal contact characterizes Schwann cells in benign and malignant peripheral nerve sheath tumors (MPNST) from neurofibromatosis type 1 (NF1) patients. Tumor Schwann cells demonstrate NF1 mutations, elevated Ras activity, and aberrant epidermal growth factor receptor (EGFR) expression. Using cDNA microarrays, we found that brain lipid binding protein (BLBP) is elevated in an EGFR-positive subpopulation of Nf1 mutant mouse Schwann cells (Nf1(−/−) TXF) that grows away from axons; BLBP expression was not affected by farnesyltransferase inhibitor, an inhibitor of H-Ras. BLBP was also detected in EGFR-positive cell lines derived from Nf1:p53 double mutant mice and human MPNST. BLBP expression was induced in normal Schwann cells following transfection with EGFR but not H-Ras12V. Furthermore, EGFR-mediated BLBP expression was not inhibited by dominant-negative H-Ras, indicating that BLBP expression is downstream of Ras-independent EGFR signaling. BLBP-blocking antibodies enabled process outgrowth from Nf1(−/−) TXF cells and restored interaction with axons, without affecting cell proliferation or migration. Following injury, BLBP expression was induced in normal sciatic nerves when nonmyelinating Schwann cells remodeled their processes. These data suggest that BLBP, stimulated by Ras-independent pathways, regulates Schwann cell-axon interactions in normal peripheral nerve and peripheral nerve tumors.